Editorial: Smart Parking Management System Using Artificial Intelligence - Amirah (Journal of Computer Science Application and Engineering (JOSAPEN), 2024)
The escalating challenges of urban parking due to increasing urbanization and rising vehicle numbers have spurred the integration of Artificial Intelligence (AI) into parking management. This article explores the potential of a Smart Parking Management System (SPMS) driven by AI to revolutionize urban parking infrastructure. The SPMS leverages AI technologies, including advanced algorithms, machine learning models, and real-time data analytics, to intelligently monitor, allocate, and optimize parking spaces. Beyond addressing immediate concerns such as congestion and parking availability, the system aligns with broader urban development goals of sustainability and improved quality of life. The SPMS offers benefits beyond convenience, contributing to a more sustainable and eco-friendly urban environment. By optimizing traffic flow and reducing time spent searching for parking, the system aims to decrease fuel consumption, emissions, and overall environmental impact. The emergence of Internet of Things (IoT) technologies plays a crucial role, with sensors in parking spaces providing real-time occupancy information, and enabling dynamic system responses. Mobile applications and smart devices further empower users with real-time information, fostering smart and sustainable transportation habits. While the promise of AI-driven SPMS is considerable, challenges such as data privacy, security, and seamless integration into existing urban infrastructure must be addressed.